PELUANG DAN TANTANGAN TRANSFORMASI DIGITAL PADA BANK SAYRIAH INDONESIA (BSI) - Kurniati, Rini Rahayu; Febrianti, Alifvira (Jurnal Bisnis Indonesia, 2024)
Bank Syariah Indonesia (BSI) in digital transformation can prove its central role as a guardian of the growth of the sharia and halal financial ecosystem by continuing to sharpen its role in national and international financial markets. The aim of the research is to analyze the opportunities and challenges of digital transformation at Bank Syariah Indonesia (BSI). This research uses descriptive qualitative methods by collecting data using triangulation analytical techniques through BSI supervisor outlets as informants.The research results show that the opportunities for digital transformation at BSI are: First, it can launch digital services in the form of: BSI Mobile, Internet Banking, SMS Banking, and virtual assistants. Secondly, it can make it easier for customers to carry out transactions without having to go to the bank directly. Third, by incorporating Sharia concepts, it can introduce Islamic service features. Fourth, it can create a level of competition in digital services. Meanwhile, the challenges of digital transformation at BSI are: First, there is hacking, A cyber attack that has the potential to disrupt or paralyze services. Second, cyber disaster recovery to ensure the continuity of bank operations during an incident.Keywords: opportunities and challenges, digital transformation, Bank Syariah Indonesia